The newspapers in the Andalusia of beginning of the 19th century: War, public opinion and society - Bravo Caro, Juan Jesús (Historia y Comunicación Social, 2014)
Mass media will be going to know a momentum of undoubted importance in the Spain of the end of the old regime. The war of independence and the necessity of the contenders to disseminate victories against the enemy, will open a new stage, where the newspapers edited in the area south of the peninsula will have a major role in the conformacion of the public opinion. The news of the conflict, the national or internacional information and other details regarding the everyday life of the citizens, will have their reception in the pages of newspapers and weeklies published.
Keywords: Press; War of the Independence; Andalucía.